2014
DOI: 10.5116/ijme.52ec.d075
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of multicultural curriculum in medical education

Abstract: ObjectivesTo evaluate impact a multicultural interclerkship had on students’ perception of knowledge, interview skills, and empathy towards serving culturally diverse populations and role student demographics played in learning.MethodsData extracted from students’ self-reported course evaluations and pre/post questionnaires during multiculturalism interclerkship across 11 academic years. Inquired students’ opinion about four areas: effectiveness, small group leaders, usefulness, and overall experience. Subscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 13 publications
(14 reference statements)
0
20
0
3
Order By: Relevance
“…While global health is expanding in the vast majority of Schools of Public Health in the U.S., no systematic information is available on outcomes of career tracking of public health students involved in global health, global cancer research, or minority research. The information that is available from global health education is mainly focused on clinical education of medical and nursing students and residents which have shown values in career development [3, 15–17]. These studies report the importance of modifying the medical school curriculum to include global health; particularly to address disease burden, traveler’s medicine, and immigrant health [1].…”
Section: Discussionmentioning
confidence: 99%
“…While global health is expanding in the vast majority of Schools of Public Health in the U.S., no systematic information is available on outcomes of career tracking of public health students involved in global health, global cancer research, or minority research. The information that is available from global health education is mainly focused on clinical education of medical and nursing students and residents which have shown values in career development [3, 15–17]. These studies report the importance of modifying the medical school curriculum to include global health; particularly to address disease burden, traveler’s medicine, and immigrant health [1].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study has shown short-term medical interventions have led to increased cross-cultural knowledge during clerkships. 15 We believe this initial exposure to the topic is an important step in getting students to think critically about the cultural aspects of treating patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adicionalmente, no tocante às competências relacionadas à atenção das necessidades individuais de saúde, as DCN estabelecem que os cursos de Medicina devem contemplar o desenvolvimento de habilidades de realização de anamnese que considerem o contexto de vida e os elementos biológicos, psicológicos, socioeconômicos e a investigação de práticas culturais de cura em saúde, de matriz afro-indígena--brasileira e de outras relacionadas ao processo saúde-doença. Tais pressupostos remetem ao que, na literatura internacional sobre educação das profissões da saúde, é referido como competências culturais (cultural competence ou cross-cultural competence) [2][3][4][5][6] .…”
Section: Introductionunclassified